Inhibition effect of cypermethrin mediated by co-regulators SRC-1 and SMRT in interleukin-6-induced androgen receptor activation. (September 2016) - Wang, Qi; Zhou, Ji-Long; Wang, Hui; Ju, Qiang; Ding, Zhen; Zhou, Xiao-Long; Ge, Xing; Shi, Qiao-Mei; Pan, Chen; Zhang, Jin-Peng; Zhang, Mei-Rong; Yu, Hong-Min; et al.
Abstract: It is hypothesized that the pesticide cypermethrin may induce androgen receptor (AR) antagonism via ligand-independent mechanisms. The Real-Time Cell Analysis (RTCA) iCELLigence system was used to investigate the inhibitory effect of cypermethrin on interleukin-6 (IL-6)–induced ligand-independent LNCaP cell growth. Then, the mammalian two-hybrid assays were applied to clarify whether the mechanism of IL-6–induced AR antagonism of cypermethrin was associated with the interactions of the AR and co-activator steroid receptor co-activator-1 (SRC-1) and co-repressor silencing mediator for retinoid and thyroid hormone receptors (SMRT). Cypermethrin inhibited the LNCaP cell growth induced by IL-6. The interactions of AR–SRC-1 and AR–SMRT mediated by IL-6 were suppressed by cypermethrin. The results indicate that the IL-6–mediated AR antagonism induced by cypermethrin is related to repress the recruitment of co-regulators SRC-1 and SMRT to the AR in a ligand-independent manner. Inhibition of the interactions of AR–SRC-1 and AR–SMRT mediated by IL-6 contributes to the AR antagonism induced by cypermethrin. Highlights: Cypermethrin can inhibit IL-6-mediated AR activation in androgen-independent manner. Cypermethrin represses IL-6-induced cell growth using the RTCA iCELLigence system. Cypermethrin suppresses the interaction between AR NTD and co-activator SRC-1 induced by IL-6. Cypermethrin suppresses the interaction between AR NTD and co-repressor SMRT induced by IL-6.